Hepatic Cirrhosis in Nymphicus hollandicus (Cockatiel) - Da Silva Costa, João Vitor; Sano, Evelin Lurie; Cequinel Carrizo, Juliana; Prado Zufelato, Pedro Augusto; Justino, Larissa; Frederico Rodrigues Loureiro, Ana Paula; Wingeter Di Santis, Giovana; Sampaio Baptista, Ana Angelita (Acta Scientiae Veterinariae, 2026)
Background: The order Psittaciformes comprises over 350 bird species, including cockatiels (Nymphicus hollandicus), whose beauty and docility make them popular pets. Despite the availability of commercial feeds designed to meet their nutritional needs, many owners provide high-energy seed-based diets, which unfortunately cause metabolic disorders such as hepatic steatosis and cirrhosis. These conditions result from chronic hepatocyte injury and fibrosis, but documented cases of these problems in avian species are limited. This paper reports a case of hepatic cirrhosis in Nymphicus hollandicus. Case: An 11-year-old female cockatiel was subjected to necropsy after being found dead. The owner reported a month-long history of lethargy, progressing to yellowish feces, regurgitation, and dyspnea. The diet consisted primarily of commercial seed mix, rice, and occasional bread and biscuits. Water was chlorinated and unfiltered, and vitamin supplementation was sporadic. The bird lived with three other cockatiels in a cage exposed to natural light during the day and housed indoors at night. No previous health issues were noted. Gross examination revealed no external abnormalities apart from chronic hyperkeratosis on one digit. Internally, ascites was evident, with a firm, multinodular, pale yellow liver exhibiting structural loss. The lungs showed diffuse congestion and edema, but other organs showed no significant changes. Histopathology confirmed hepatic cirrhosis, with fibrous connective tissue surrounding hyperplastic hepatocyte nodules, bile duct proliferation, lymphoplasmacytic infiltration, and hepatocellular fatty degeneration. The lungs showed severe vascular congestion, while the heart exhibited no relevant alterations. Discussion: Cirrhosis, which is rarely reported in birds, typically arises from chronic inflammation and poor dietary management. Unlike mammals, avian species lack an extensive lymphatic system, making their livers more susceptible to lipid accumulation from high-fat diets. Seed-based diets, deficient in proteins, vitamins, and minerals, exacerbate triglyceride buildup in hepatocytes, leading to hepatic steatosis and eventually, cirrhosis. Similar cases in Amazona aestiva and Psittacus erithacus reinforce the association between poor diet and liver pathology. The bird’s dyspnea was likely due to ascites-related respiratory distress, a common sequela of hepatic failure in birds, attributed to portal hypertension and decreased colloid osmotic pressure from hypoproteinemia. The presence of biliverdin-stained feces further supported hepatobiliary dysfunction. Diagnosis of hepatic diseases in birds is challenging because enzyme alterations are often nonspecific. While radiography, endoscopy, and biopsy aid in diagnosis, they are mostly available in specialized centers. Management of avian hepatic cirrhosis focuses on diet correction and hepatoprotective therapies, including plant extracts and probiotics, which show promise in modulating the progression of liver disease. Despite advances in avian nutrition, many pet cockatiels continue to receive imbalanced diets due to owner misinformation and the affordability of seeds. Nutritional mismanagement remains a primary factor in psittacine metabolic disorders, necessitating increased awareness and dietary adjustments to prevent conditions like steatosis and cirrhosis. This case underscores the consequences of inadequate nutrition, ultimately leading to fatal hepatic cirrhosis in Nymphicus hollandicus. Keywords: necrosis, fibrosis, steatosis, ascites, diet.